The association between platelet transfusion and idiopathic pneumonia syndrome is unaffected by platelet product type. Issue 2 (4th October 2015) - Vande Vusse, Lisa K.; Madtes, David K.; Bolgiano, Douglas; Watkins, Timothy R.
Abstract : BACKGROUND: Methods used to produce platelet (PLT) components, pooling of PLT‐rich plasma (PRP‐PLT) and apheresis (AP‐PLT), may variably contribute to the pathogenesis and severity of idiopathic pneumonia syndrome (IPS). STUDY DESIGN AND METHODS: We performed a retrospective cohort study of 906 allogeneic hematopoietic cell transplant recipients to examine associations between PLT product type and risks of developing IPS and dying after IPS onset. Proportional hazards models included separate terms for the sum of all PLT transfusions and the sum of PRP‐PLT units received in the 3 or 7 days before IPS onset. Similarly constructed models analyzed the outcome of time to death after IPS onset. All analyses were adjusted for known IPS risk factors. RESULTS: Patients received a median of three PRP‐PLT transfusions (interquartile range [IQR], 0‐6) and five AP‐PLT transfusions (IQR, 1‐13) while at risk for IPS. Seventy‐five patients (8%) developed IPS by Posttransplant Day 120. The proportion of PRP‐PLT transfusions was not associated with risk of developing IPS (3‐day hazard ratio [HR] 0.98, 95% CI 0.74‐1.29, p = 0.86; 7‐day HR 1.00, 95% CI 0.86‐1.15, p = 0.95) or dying after IPS onset (3‐day HR 0.99, 95% CI 0.75‐1.31, p = 0.97; 7‐day HR 0.98, 95% CI 0.78‐1.12, p = 0.47). CONCLUSION: The association between PLT transfusions and risk of developing IPS or dying after IPS onset does not differ according to PLT product type. Further research is required to identify potentially modifiable steps in PLT component production that contribute to IPS.